Children's Rights at the Crossroads: The Challenge of Anti-Trans Legislation in Alberta Schools - Anderson, Jamie; Campbell, Caitlin; Richard, Nicole; Callaghan, Tonya (Journal of Contemporary Issues in Education, 2025)
Significant barriers to inclusion persist for 2SLGBTQIA+ children in Alberta, with legislation limiting school support for 2SLGBTQIA+ students taking effect in the province in 2025. Transgender and non-binary identities are specifically targeted by this legislation, with the government restricting the ability for youth to use different names or pronouns at school without prior parental permission. Tensions between parental rights claims and children’s rights have a long history in Alberta discourses, but there is a growing movement in education policymaking across Canada and the United States that seeks to elevate parental rights into law. Parental rights movements refute the rights of children as enumerated in the United Nations Convention on the Rights of the Child and seek control over their sexual orientation and gender identity. Through a narrative literature review and Critical Discourse analysis, we examine the key values concerning children’s rights and parental rights that underpin anti-trans policymaking in the Alberta context and explore pedagogical possibilities that center children’s rights in anti-trans school contexts.